Digital Recording and Documentation of Endoscopic Procedures: Do Patients and Doctors Think Alike? - Nadav Willner; Maya Peled-Raz; Dan Shteinberg; Michal Shteinberg; Dean Keren; Tova Rainis (Canadian Journal of Gastroenterology and Hepatology)
Aims and Methods. Conducting a survey study of a large number of patients and gastroenterologists aimed at identifying relevant predictors of interest in digital recording and documentation (DRD) of endoscopic procedures. Outpatients presenting to the endoscopy unit at our institution for an endoscopy examination were anonymously surveyed, regarding their views and opinions of a possible recording of the procedure. A parallel survey for gastroenterologists was conducted. Results. 417 patients and 62 gastroenterologists participated in two parallel surveys regarding DRD of endoscopic procedures. 66.4% of the patients expressed interest in digital documentation of their endoscopic procedure, with 90.5% of them requesting a copy. 43.6% of the physicians supported digital recording while 27.4% opposed it, with 48.4% opposing to making a copy of the recording available to the patient. No sociodemographic or background factors predicted patient’s interest in DRD. 66% of the physicians reported having recording facilities in their institutions, but only 43.6% of them stated performing recording. Having institutional guidelines for DRD was found to be the only significant predictor for routine recording. Conclusions. Our study exposes patients’ positive views of digital recording and documentation of endoscopic procedures. In contrast, physicians appear to be much more reluctant towards DRD and are centrally motivated by legal concerns when opposing DRD, as well as when supporting it.